Dialogando com adolescentes sobre educação em saúde: a contribuição da musicoterapia comunitária - Mayer, Graziela Carla Trindade (Universidade do Vale do Rio dos Sinos, 2015)
This study aimed to learn about health conceptions and practices from references provided by teenagers, in the school context, in dialogue with the complex network of relations that they establish with the world and in particular with their expressions and musical identities. The potentialities in the development of health education processes through Community Music Therapy (MT) with teenagers in a school environment were investigated. A qualitative study was conducted supported by assumptions of an action-research and developed through a participatory methodology. Four methods of Music therapy were used in the meetings, as stated by Bruscia (2000): improvisation, composition, recreation and hearing. The fieldwork took place between the months of September to December 2014 in a municipal primary school located in São Leopoldo, in Rio Grande do Sul. 12 teenagers aged 13 to 18 took part in the research. All the meetings were recorded for the purpose of registering the contents developed by the researcher and the questions of the participants. The analytical process took double movement, incorporating the findings, knowledge and actions produced by the teenage researchers and the qualitative analysis (MINAYO, 2006). The results of the study suggest that teenagers have different and contradictory meanings to health, transiting between the representations and practices of the hegemonic pattern present in the biomedical model of health and the group projections associated with the expanded concept of health. These projections bring up values such as the self-care, caring for the others, above all, friends and family, extending to the care with the school and with the territory. This way, school takes a privileged role in human development, such as in the promotion of life and in the care with the health of their students. However, it is necessary to incorporate this look in their pedagogical practices, in the management of space and environment that is shared by all of them. In order to do it, it is possible to make use of the school community, participation of the students and of the contribution of the other equipment in its territory. Among them, the health network system has clinical and sanitary responsibility for developing actions for promotion and prevention inside and outside the school. It is a matter of intersectoral dialogue that needs to connect health needs with solving. More than learning the meaning and the health practices of teenagers, there is a need to recognize them as producers of knowledge and health practices, making the spaces of the school environment as the territorial neighborhood. Otherwise, we will keep the culture of fragmentation, preventing caring from being accessible in the right time and fully, which can even mean irreversible damage or loss for teenagers.
Keywords: Educação em saúde; Adolescentes; Musicoterapia comunitária; Escola; Health education; Teenagers; Community music therapy; School; ACCNPQ::Ciências da Saúde::Saúde Coletiva